Experimental investigation on the quality of electric discharge machined Ti-6Al-4V using bio-oil and biodiesel. (2021) - Basha, S.M.; Dave, H.K.; Patel, H.V.
Abstract: Titanium grade 5 supper alloy is widely used in the aerospace, automobile, and medical industries due to its properties like high specific strength, high hot hardness, biodegradability, excellent wear, and corrosion resistance. Owing to higher hardness, it is very difficult to machine by traditional machining processes like turning and milling. Electric discharge machining (EDM) is an advanced, non-contact, and thermal energy based machining process where material removal takes place due to the melting and vaporization of workpiece material. Dielectric fluid is an inevitable component in the EDM process. Generally, hydrocarbon based dielectric fluids are used in the EDM process where the emissions generated are carcinogenic. To avoid these hazardous emissions and to make the EDM process more sustainable, in this work, an attempt is made to investigate Jatropha Curcas based bio-oil and biodiesel as a dielectric medium. Taguchi L16 experimental plan is used to investigate the effect of process parameters on surface roughness and overcut. Analysis of Variance (ANOVA) is carried out on the experimental data to find the significance level and the degree of the contribution of each process parameter.